AN OVERVIEW OF SMART PHONE-BASED POCKET FALL ACCIDENT DETECTION, POSITIONING AND RESCUE SYSTEM - MR. MOMIN FAISAL AHMED; MR. D.L GADHE; MR. MAZHER KHAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The smart phones have developed very rapidly and have become the basic need of the today’s smart world. The accidents are too often occurring in the fast lifestyle. In the country like India, the smart phones are available in huge number. India has around 200 million smart phone users. Due to this huge number of users its need of time to develop some smart applications using the smart phones for the betterment of human. The severity of any human fall events can be reduced by the detection of event smartly. The motion of the body is detected by using small electromechanical systems. The different motion sensors are used for these applications. Authors have proposed the system where the global positioning system is applied for the identification of human fall event occurrence. To make the system effective along with GPS authors have used GPS systems too to transmit the data of fallen human. Due to this the help will be provided to the human on priority basis.